PENGARUH METODE FISH BOWL TERHADAP BERFIKIR KRITIS SISWA PADA MATA PELAJARAN SEJARAH KELAS XI IPS SMAN 8 KOTA JAMBI - Pratiwi, Diah; Rahim, Arif (Universitas Batanghari Jambi, 2022)
This study aims to determine whether there is an effect of the Fish Bowl method on students' critical thinking in the history subject of class XI IPS SMAN 8 Jambi City in the academic year 2021/2022? This type of research is a quasi-experimental (Quasi Experimental Design). The total population in this study was 284 people. The sampling technique in this study was simple random sampling, so that 35 students of class XI IPS 4 were selected as the control class and 35 students of class XI IPS 5 were selected as the experimental class. The data collection technique in this research is by distributing questionnaires to research respondents and documentation. The data analysis technique in this study was the t-test using the SPSS For Windows Version 16 program. The results showed that (1) the results of the Pre-Test & Post-Test Experimental Class obtained a total score of 4187. (2) the results of the Pre-Test & Post-Test The Control Class Test obtained a total value of 3344. Furthermore, it can be seen by the analysis used using the Normality Test withJurnal IstoriaProdi Pendidikan Sejarah E-ISSN 2597-8845FKIP Universitas Batanghari Jambi Vol. 6 No. 2. September 202275the results of the significance value, 0.040 > 0.05. So it can be concluded that the residual value is normally distributed, followed by homogeneity test analysis with the results of Sig. Levene statistic > 0.05 ie 0.280 > 0.05. Thus, it can be concluded that the research data is homogeneous, and the t-test is -34.104 and the sig value is 0.000. So, the value of Sig. 0.000 <0.05 then Ho is rejected. That is, there is a significant influence on the use of the Fish Bowl learning model on students' critical thinking in history subjects. Based on the results of the research that the researchers obtained, it can be concluded that there is an effect of using the Fish Bowl Method on students' critical thinking in the history subject of class XI SMAN 8 Jambi City.